Cost–Benefit Analysis of in vivo Reflectance Confocal Microscopy for Melanoma Diagnosis in a Real-World Clinical Setting - Bruno GM; Di Matteo S; Longo C; Stanganelli I; Farnetani F; Borsari S; Mazzoni L; Ciardo S; Raucci M; Magi S; Bassoli S; Spadafora M; et al. (Risk Management and Healthcare Policy)
Giacomo Matteo Bruno,1 Sergio Di Matteo,2 Caterina Longo,3,4,* Ignazio Stanganelli,5,6,* Francesca Farnetani,7 Stefania Borsari,3 Laura Mazzoni,5 Silavana Ciardo,7 Margherita Raucci,3 Serena Magi,5 Sara Bassoli,7 Marco Spadafora,3,8 Victor Desmond Mandel,9 Alice Casari,7 Johanna Chester,7 Shaniko Kaleci,7 Giorgio Lorenzo Colombo,10 Giovanni Pellacani11 1Department of Drug Sciences, University of Pavia, Pavia, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche S.r.l., Health Economics & Outcomes Research, Milan, Italy; 3Azienda Unità Sanitaria Locale – IRCCS di Reggio Emilia, Skin Cancer Center, Reggio Emilia, Italy; 4Department of Dermatology, University of Modena and Reggio Emilia, Modena, Italy; 5Skin Cancer Unit, IRCCS Istituto Romagnolo per lo Studio dei Tumori (IRST) “Dino Amadori”, Meldola, Italy; 6Department of Medicine and Surgery, University of Parma, Parma, Italy; 7Dermatology Unit, Department of Surgical, Medical, Dental & Morphological Sciences with Interest Transplant, Oncological & Regenerative Medicine, University of Modena and Reggio Emilia, Modena, 41125, Italy; 8Clinical and Experimental Medicine PhD Program, University of Modena and Reggio Emilia, Modena, Italy; 9Porphyria and Rare Diseases Unit, San Gallicano Dermatological Institute-IRCCS, Roma, Italy; 10Department of Drug Sciences, CEFAT-Center of Pharmaceuticals Economics and Medical Technologies Evaluation, University of Pavia, Pavia, Italy; 11Department of Clinical Internal, Anesthesiological and Cardiovascular Sciences, Dermatology Clinic, Sapienza University of Rome, Rome, Italy*These authors contributed equally to this workCorrespondence: Giacomo Matteo Bruno, Department of Drug Sciences, University of Pavia, Pavia, Italy, Email giacomomatteo.bruno@unipv.itBackground: In a recent prospective, multicenter, two-arm randomized controlled trial (RCT), we demonstrated that adjunctive reflectance confocal microscopy (RCM) in routine clinical practice provides clinical benefits, including safe melanoma detection and a 43.3% reduction in the number needed to excise (NNE).Methods: A cost–benefit analysis was conducted based on NNEs for standard care (5.3) and adjunctive RCM (3.0). Cost data were supplied by one center, applying a micro-costing approach from the hospital’s perspective. Costs were calculated for dermatology exams, excisions, medications, histopathology, and follow-up. The outcomes were extrapolated to provincial and national settings to assess the economic benefits of RCM.Results: The cost per patient for standard care was € 143.63, compared to € 114.74 for adjunctive RCM. The cost per melanoma excised with standard care (NNE 5.3) was € 904.87, almost twice the cost for RCM (€ 458.96). Annual regional and national costs for standard care were € 864,150.85 and € 11,491,849.00, respectively, while RCM reduced these to € 438,306.80 and € 5,828,792.00. Estimated annual savings with adjunctive RCM were € 425,844.05 regionally and € 5,663,057.00 nationally. The cost–benefit ratio for RCM was 3.89, meaning that for every € 1 spent on RCM, there is a benefit of € 3.89.Conclusion: In real-world clinical practice, adjunctive RCM offers significant economic advantages at local, regional, and national levels while maintaining patient safety and reducing unnecessary surgical procedures.Keywords: melanoma, dermoscopic examination, reflectance confocal microscopy, cost–benefit, economics, cost analysis, skin cancers